Krytyka romansu tradycyjnego w publicystyce oświeceniowej = Criticism of traditional romance in Enlightenment publishing - Siama, Alfred (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The main topic of the article is the attitude of the 18th century publicists to traditional romance. The work points to selected judgments about this literary genre present in the encyclopedic and journalistic texts of the Enlightenment. Some similarities in the perception of the genre, as well as some discrepancies in how the intellectuals of the era comprehended this term were indicated.
Keywords: romans tradycyjny; oświecenie; publicystyka; krytyka; traditional romance; Enlightenment; journalism; criticism